Peran Konseling Dalam Mengatasi Depresi Pada Remaja Usia 10-24 Tahun (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
An adolescent is someone between the ages of 10-24 years, which is a process of self-development where a person experiences the process of not being a child anymore and heading towards adulthood but cannot be said to be a mature adult and is someone who has not entered the category of marriage during that period. While depression itself is a condition in which a person who experiences emotionally characterized by sadness and feelings of meaninglessness and guilt, distancing himself from the environment, losing appetite, not being able to sleep peacefully and experiencing anxiety. In this study, researchers discussed how the role of counseling can overcome depression in adolescents where there is a very important role of counselors in helping and overcoming the problems of clients experiencing depression.